The Intracluster Light Analysis of the Most Evolved Systems of Galaxies: Fossil Groups - Nícolas O. L. de Oliveira; Yolanda Jiménez-Teja; Renato A. Dupke; Eleazar R. Carrasco; Anton M. Koekemoer; Yuanyuan Su; Jose Manuel Vilchez; Jimmy A. Irwin; Eric D. Miller; Lucas E. Johnson (The Astrophysical Journal Letters, 2025)
We present the analysis of the intracluster light (ICL) in three fossil groups, RX J085640.72+055347.36, RX J1136+0713, and RX J1410+4145, at z ∼ 0.1. We used two optical broadband filters, F435W and F606W, observed with the Hubble Space Telescope, and spectroscopic data obtained with the Gemini Multi-Object Spectrograph to generate the ICL maps and measure the ICL fraction using CICLE, an algorithm developed to disentangle the ICL from the light of galaxies. We found ICL fractions of 9.9%–14.4%, 3.8%–6.1%, and 4.7%–10.7% for RXJ0856, RXJ1136, and RXJ1410, respectively. This behavior is not consistent with the presence of the ICL fraction excess previously observed in merging clusters, and is also inconsistent with the constant ICL fraction distribution characteristic of relaxed systems, although the values found are within the typical range expected for the latter. Instead, they show a significantly increasing trend with wavelengths over ∼3800–5500 Å, indicating that fossil groups are indeed old and undisturbed systems, even compared with regular relaxed clusters.